2018
DOI: 10.15406/htij.2018.06.00169
|View full text |Cite
|
Sign up to set email alerts
|

Normal complete blood count reference intervals in the Turkish population: a prospective study

Abstract: This study aim to analyze and report the normal complete blood count (CBC) reference intervals in the Turkish population. 1375 healthy people living in Manisa-Turkey, nonpregnant, with no known disease, with no pathological entity in physical examination and anamnesis, with no medicine usage in the last 15 days, stating that they and also their first degree relatives do not have any blood diseases, were included in the study. Vitamin B12, folic acid, ferritin levels were analyzed for each of the participants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…In this study, males were shown to have higher RBC parameter values than females, while females had higher WBC and platelet counts than males. These findings are similar to those reported in other countries such as Ghana, 7,8 Turkey, 9 Malaysia, 10 China, 11 and the United Kingdom. 12 It is well known that the differences in RBC values between males and females are primarily due to the influence of the androgenic hormone on erythropoiesis and the menstrual blood loss in females.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, males were shown to have higher RBC parameter values than females, while females had higher WBC and platelet counts than males. These findings are similar to those reported in other countries such as Ghana, 7,8 Turkey, 9 Malaysia, 10 China, 11 and the United Kingdom. 12 It is well known that the differences in RBC values between males and females are primarily due to the influence of the androgenic hormone on erythropoiesis and the menstrual blood loss in females.…”
Section: Discussionsupporting
confidence: 91%
“…MPV is the mean size of platelets calculated by hem counter and PCT is calculated automatically by (MPV x platelet count)/10000 formula. Normal median values of MPV and PCT in Turkish population were found as 7.5-12 fl and 0.239 [6] [7] . Alterations of MPV along with platelets have been linked to various diseases associated with inflammation [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional anemia is the most common type of anemia in children. However, thalassemia minor carriage is one of the most common causes of anemia in Türkiye and Mediterranean countries (Kabasakal et al, 2018;Arslan Maden et al, 2020). Thalassemia major, thalassemia intermedia, and thalassemia minor are the three main types.…”
Section: Introductionmentioning
confidence: 99%